Acute Respiratory Distress Syndrome Induced by E-Cigarette or Vaping Product Use Associated Lung Injury - Suherman, Intan; Purwanti, Efi; Fakhrury, Rey Mas; Firmansyah, Sidik (PT Inovasi Pratama Internasional, 2023)
In 2019, a respiratory infection outbreak in individuals with a history of vaping was discovered, This condition was eventually termed e-cigarette or vaping product use–associated lung injury (EVALI) after it was linked to lung damage during imaging and histopathologic examination. The exact mechanism behind the lung injury seen in EVALI is unknown. Several studies show that EVALI has been associated with the incidence of acute respiratory distress syndrome. Nowadays, many people use Vapes/e-cigarettes, it is critical for clinicians to understand the hazards of using e-cigarettes, which can induce EVALI to ARDS. We used a number of research resources, including ScienceDirect, Google Scholar, PubMed, and Wiley, to search, select, and choose papers about the use of electronic cigarettes or vaping devices associated to lung injury trigger Acute Respiratory Distress syndrome. The literature search yielded 330 articles, of which 21 met the selection criteria based on the title and abstract. EVALI is still a clinical diagnosis that should be considered as an exclusion because the symptoms, physical examination, serologic, radiologic, and bronchoscopy results are not specific to the illness alone. ARDS and its sequelae may be more likely to occur in patients with EVALI who also have several chronic illnesses. For individuals who use excessively and consistently over weeks or months, there is strong correlative evidence suggesting a higher risk of VAPI and potential consequences from ARDS in the absence of prompt and aggressive therapy.